2023
DOI: 10.1002/cbm.2286
|View full text |Cite
|
Sign up to set email alerts
|

Economic evaluations of mental health interventions in criminal justice

Abstract: Background: Mental health interventions targeting crime perpetrators are available. An overview of the current scenario of their economic benefits will help policy decisions. Aim: To provide an update on economic evidence for mental health interventions in criminal justice, and to identify challenges and responses in using economic evidence to inform policy. Method: Narrative review with an analysis frame that organises evidence around four points on the criminal justice system pathway: (a) point of contact; (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Considering the costs of imprisonment, reduced recidivism will lead to financial impacts on the CJS. There is also evidence of cost-effectiveness in providing mental health interventions and treatment during incarceration and post-incarceration [ 41 ]. Providing mental health services and programs in prison and after release is a legal (societal and humanitarian) imperative and a way to improve individuals’ skills and coping strategies to increase their successful reintegration into society after prison release (and, therefore, decrease reoffending and recidivism rates).…”
Section: Discussionmentioning
confidence: 99%
“…Considering the costs of imprisonment, reduced recidivism will lead to financial impacts on the CJS. There is also evidence of cost-effectiveness in providing mental health interventions and treatment during incarceration and post-incarceration [ 41 ]. Providing mental health services and programs in prison and after release is a legal (societal and humanitarian) imperative and a way to improve individuals’ skills and coping strategies to increase their successful reintegration into society after prison release (and, therefore, decrease reoffending and recidivism rates).…”
Section: Discussionmentioning
confidence: 99%
“…Suicide rates among UK prisoners were previously reported at 3.9 times those of the general population (Office for National Statistics [ONS], 2023 ), highlighting a need for cost-effective interventions to address prisoners adverse mental health. A recent review by Knapp and Wong ( 2023 ) aimed to provide an update on economic evidence for mental health interventions across the criminal justice system and summarised that there is a paucity of high-quality economic evidence (Knapp & Wong, 2023 ). However, the review was narrative in focus and did not include a formal quality assessment.…”
mentioning
confidence: 99%
“…costs alone or outcomes alone) may be available, they do not allow us to consider value for money. The review also aimed to formally appraise the quality of identified evidence and highlight research gaps (to inform future research), addressing one of the key limitations identified with the recent review by Knapp and Wong ( 2023 ). Figure 1 depicts the flow of studies through the review process.…”
mentioning
confidence: 99%